Microfoundations of strategic problem formulation - Baer, Markus; Dirks, Kurt T.; Nickerson, Jackson A. (Strategic Management Journal, 2013)
Before a strategy can be developed, the problem it is supposed to address needs to be formulated. We establish the microfoundations of strategic problem formulation by developing a theory that predicts a core set of impediments to formulation that arise when complex, ill‐structured problems are addressed by heterogeneous teams. These impediments fundamentally constrain and narrow problem formulation, thereby limiting solution search and potential value creation. We establish these impediments as a set of design goals, which, if remedied by an appropriately constructed mechanism, can expand problem formulation to be more comprehensive. Finally, we consider how organizations can improve problem formulation by creating a structured process that satisfies the theoretically derived design goals and detail a specific example of this mechanism (collaborative structured inquiry). Copyright © 2012 John Wiley & Sons, Ltd.